Parental Leave from the Firm's Perspective - Gozde Corekcioglu; Marco Francesconi; Astrid Kunze (Institute of Labor Economics (IZA), 2025)
This study investigates the firm's response to parental leave induced worker absence. Combining a 20-week maternal leave expansion in Norway and detailed matched employer-employee data between 1983 and 2013, we identify the causal impact of absence on outcomes using a shift-share design. Employers with greater exposure to absence hire more women aged 40 or less and face more employment turnover. These adjustments do not affect profits, but lead to greater investments and sales and to a lower value added and a lower wage bill. One important channel behind such changes is a significant growth of young female part-time employment.
Keywords: L23; L25; J16; J21; J23; J81; 330; employer-employee matched data; part-time employment; corporate outcomes; firm-level gender employment dynamics; workforce composition; shift-share research design